Nutritional therapy as a strategy for food selectivity in autistic children (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is a human neurodevelopmental disorder that causes impairment in communication and social interaction. Individuals with ASD present repetitive and restrictive behavior patterns, with repercussions in the area of nutrition, since food selectivity and the presence of gastrointestinal problems are recurrent among sufferers. This literature review aimed to analyze food selectivity and disorders or changes in the sensory process in children with ASD. Studies in English and Portuguese from the SCIELO, CAPES, APA, EBSCO host International Journals databases were used. After analyzing studies that report on the habits and nutritional status of children who developed food selectivity or refusal, it was found that nutritional therapy has been an effective strategy in the treatment of food selectivity in autistic children. It was found that to date, there is no diet therapy implemented. The different characteristics of the disorder in terms of behavior and sensory aspects require an individualized look and respect for each case in a unique and particular way. Scientific literature has shown, in relation to food, that the three most striking aspects are: selectivity, refusal and indiscipline.